Ocena obciążenia współczynników współzależności dla tablic kontyngencji - Domański, Czesław; Stepień, Lechosław (Estimation of the bias of correlation coefficients for contingency tables, 2006)
In the article the bias of six chosen correlation measures for 2x2 contingency tables is assessed with the use of the Taylor expansion. To illustrate obtained results, the estimated bias of the Q Yule measure was presented in relation to the sample size and to the distribution of the probabilities of variables investigated. The results of calculations indicate that the bias of the estimator of the g-Yule measure is very small for symmetric distributions whereas for asymmetric ones it is large. Values of the bias decrease together with the increase of the sample size.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 9-16